The ultrasound assessment of the psoriatic arthritis: from joint to skin - A. Ariani; A. Becciolini; C. Bertolazzi; R. De Angelis; E. Filippucci; M. Gutierrez; W. Grassi (PAGEPress Publications, 2011)
There is a growing number of papers investigating the diagnostic potential of ultrasonography in the assessment of patients with psoriatic arthritis and supporting its higher sensitivity over clinical examination in the diagnosis of synovitis, enthesitis and tenosynovitis. Less attention has been paid on both skin and nail, frequently involved in this condition. The aim of this paper is to show the potential of ultrasound in a multi-target assessment (joints, tendons, entesis, skin and nails) in patients with psoriatic arthritis, using the last generation ultrasound equipment.